Estrogen Receptor β2 Oversees Germ Cell Maintenance and Gonadal Sex Differentiation in Medaka, Oryzias latipes - Chakraborty, Tapas (Stem Cell Reports, 2019)
In vertebrates, estrogen receptors are essential for estrogen-associated early gonadal sex development. Our previous studies revealed sexual dimorphic expression of estrogen receptor β2 (ERβ2) during embryogenesis of medaka, and here we investigated the functional importance of ERβ2 in female gonad development and maintenance using a transgenerational ERβ2-knockdown (ERβ2-KD) line and ERβ2-null mutants. We found that ERβ2 reduction favored male-biased gene transcription, suppressed female-responsive gene expression, and affected SDF1a and CXCR4b co-assisted chemotactic primordial germ cell (PGC) migration. Co-overexpression of SDF1a and CXXR4b restored the ERβ2-KD/KO associated PGC mismigration. Further analysis confirmed that curtailment of ERβ2 increased intracellular Ca(2+) concentration, disrupted intra- and extracellular calcium homeostasis, and instigated autophagic germ cell degradation and germ cell loss, which in some cases ultimately affected the XX female sexual development. This study is expected improve our understanding of germ cell maintenance and sex spectrum, and hence open new avenues for reproductive disorder management.